Prophylactic host behaviour discourages pathogen exploitation. (21st October 2020) - Mitchell, Evan; Wild, Geoff
Highlights: How does prophylactic host behaviour affect the evolution of an infectious disease? The suite of prophylactic host behaviours comprises the "behavioural immune system". We find prophylactic host behaviour selects for lower exploitation by pathogens. Lower exploitation shields the pathogen from the host behavioural immune system. Abstract: Much work has considered the evolution of pathogens, but little is known about how they respond to changes in host behaviour. We build a model of sublethal disease effects where hosts are able to choose to engage in prophylactic measures that reduce the likelihood of disease transmission. This choice is mediated by utility costs and benefits associated with prophylaxis, and the fraction of hosts engaged in prophylaxis is also affected by population dynamics. When prophylactic host behaviour occurs, we find that the level of pathogen host exploitation is reduced, by the action of selection, relative to the level that would otherwise be predicted in the absence of prophylaxis. Our work emphasizes the significance of the transmission-recovery trade-off faced by the pathogen and the ability of the pathogen to influence host prophylactic behaviour.